Pengaruh Kualitas Sumber Daya Manusia Terhadap Peningkatan Pelayanan Di Kelurahan Mustikasari Kota Bekasi - Veronika Yuni T; Lia Marthalia; Ratna Kusuma Dewi (Jurnal Minfo Polgan, 2024)
This study aims to lookat performance and governance in the implementation of servise activities to public, and also relationships with leaders and fellow employees. Improving the quality of servise, must always pay attention to the demands and dynamics of the people who are in an atmosphere must pay attention to the demandsand dynamic of people who are in an atmosphere of Europhoria reform, democracy, democratization, decentralization, regional autonomy and human rights enforcement, intended to anticipate the advancement of scienceand technology. Therefore, improving the quality of service is a continuous, on going effort and is carried out by all government officials in the City of Bekasi